Environmental (re)qualification of springs as an instrument of urban resilience: the case of the Lageado watershed, São Paulo/SP - Silva, Luciano Abbamonte da; Koury, Ana Paula (Scientific Journal ANAP, 2025)
Objective – Deepen the understanding of the constitution, in terms of environmental characteristics, of the set of springs that make up the Ribeirão Lageado watershed.Methodology – Empirical case study, whose theoretical approach underpins the analysis of field visits and the systematization of data generated for each of the twenty springs.Originality/Relevance – The study allowed the collection of a series of evidence that demonstrates how the accelerated urbanization process of the outskirts of São Paulo is taking place, whose interventions, in their rapid advancement, seem to escape official records.Results – The twenty springs were named, based on prominent elements of the road layout, which were categorized according to the environmental requalification potential of each one, whether high, medium or low.Theoretical/Methodological Contributions – The study presents a relatively quick exercise, but one that manages to fill, in terms of a planned preliminary analysis, gaps and outdated information in official records.Social and Environmental Contributions – The study demonstrates, from an environmental perspective, that each sub-basin of the system can be understood, and qualified, as a minimum unit of urban planning.
Keywords: Environmental requalification; Urban resilience; SDG 11